2016
DOI: 10.11604/pamj.2016.23.206.7041
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors and assessment for cardiovascular disease among HIV-positive patients attending a Nigerian tertiary hospital

Abstract: IntroductionCardiovascular risk factors are prevalent in HIV-positive patients which places them at increased risk for cardiovascular disease (CVD). We aimed to determine the risk factors and risk assessment for CVD in HIV-positive patients with and without antiretroviral therapy.MethodsThis was a cross-sectional study of HIV-positive patients attending the Lagos University Teaching Hospital, Nigeria. Anthropometric and blood pressure measurements were performed; fasting lipid profile, plasma glucose, homocyst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
17
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 41 publications
2
17
0
2
Order By: Relevance
“…Eight studies reported on DM [ 22 24 , 27 30 , 33 ], and 3 of these studies found statistically higher odds of DM in patients on ART ( Table 3 & Fig 3 ) [ 27 , 29 , 33 ]. Overall, there was no statistically significant association between DM and ART use (Pooled estimate: 2.53, 95% CI: 0.87–7.35, p = 0.089), and a significant between-study heterogeneity (p<0.001, I 2 statistic = 70.7%).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Eight studies reported on DM [ 22 24 , 27 30 , 33 ], and 3 of these studies found statistically higher odds of DM in patients on ART ( Table 3 & Fig 3 ) [ 27 , 29 , 33 ]. Overall, there was no statistically significant association between DM and ART use (Pooled estimate: 2.53, 95% CI: 0.87–7.35, p = 0.089), and a significant between-study heterogeneity (p<0.001, I 2 statistic = 70.7%).…”
Section: Resultsmentioning
confidence: 99%
“…All 8 studies that reported on total cholesterol found higher odds of having a high TC level in patients receiving ART compared to ART-naïve patients [ 18 , 23 , 25 , 28 , 30 , 33 35 ]. The overall pooled estimate was 3.85 (95% CI: 2.45–6.07, p<0.001), the between study heterogeneity p = 0.003 and I 2 statistic = 67.0%.…”
Section: Resultsmentioning
confidence: 99%
“…The prevalence of hypertension in PLHIV is estimated to range from 9 to 46% in low-and middle-income countries (LMICs) [13,14], similar to high-income countries [15][16][17]. Patients on ART are more likely to have dysglycemia, hypertriglyceridemia, and lower levels of high-density lipoprotein cholesterol [18][19][20], which may increase hypertension risk. Also relevant, studies indicate that HIV may increase the risk of non-communicable disease (NCD), including cardiovascular disease CVD, due to stimulation of inflammatory markers and adverse events of ART [21][22][23][24].…”
Section: Introductionmentioning
confidence: 99%
“…Risk factors and risk assessment for cardiovascular diseases are increased in HIV-positive patients with and without antiretroviral therapy. These factors include hypertension, measures of obesity, diabetes mellitus, dyslipidaemia, and homocysteine [26]. Electrocardiography is effectively used to detect cardiac Diseases.…”
Section: Human Immunodeficiency Virus (Hiv)mentioning
confidence: 99%